The role of waqf in socio-economic development: case study of waqf organizations in the UK - Mazrul Shahir, Md Zuki; Mohyin, Nur Affah (Institut Kajian Zakat Malaysia (IKaZ), 2013)
Waqf has always been an important institution that contributes to the development and growth of the social economic environment. Historically, it has been proven that waqf plays an essential role in developing various aspects of education, the economy and society. Accordingly, this research aims at identifying the current role of waqf and its contribution towards socio-economic development, specifically in the United Kingdom (UK). A qualitative approach was adopted to achieve the research aim. Three in-depth case studies were conducted involving three waqf organizations in the UK: 1. Islamic Relief; 2. Europe Trust; and 3. The Islamic Foundation. The case studies involve in-depth interviews with the general director, the deputy director and the finance manager, while supporting data was collected from documented analysis of all available and relevant printed information including the organizations’ websites. The findings highlight the importance of waqf in developing social economics. The first waqf organization concentrates on emergency relief and sustainable health, nutrition, livelihood, orphans and child welfare; the second organization supports youth, community and organizations, while the third organization focuses more on research, education, publications and da'wah. Finally, the paper concludes with limitations and implications of the findings that provide a sound platform for future research.